Cellular Lnc_209997 suppresses Bombyx mori nucleopolyhedrovirus replication by targeting miR‐275‐5p in B. mori. Issue 3 (2nd February 2022) - Lin, Su; Zhang, Shao Lun; Yin, Hao Tong; Zhao, Zhi Meng; Chen, Zi Kang; Shen, Man Man; Zhang, Zheng Dong; Guo, Xi Jie; Wu, Ping
Abstract: Long non‐coding RNA (lncRNA) is a type of non‐coding RNA molecule, which exceeds 200 nucleotides in length and participates in the regulation of a variety of life activities. Recent studies showed that lncRNAs play important roles in viral infection and host immunity. At present, the researches on insect lncRNAs are relatively few. In this study, we found the expression of Lnc_209997 was significantly down‐regulated in silkworm fat body infected with Bombyx mori nucleopolyhedrosis virus (BmNPV). Inhibition of Lnc_209997 promoted BmNPV replication. Enhancing the expression of Lnc_209997 inhibited the proliferation of BmNPV. miR‐275‐5p was up‐regulated in silkworm fat body infected with BmNPV. Dual luciferase reporter gene system confirmed the interaction between Lnc_209997 and miR‐275‐5p. Over‐expression of Lnc_209997 inhibited the expression of miR‐275‐5p, while inhibition of Lnc_209997 enhanced the expression of miR‐275‐5p. Further, over‐expression of miR‐275‐5p can facilitate the replication of BmNPV. These results suggested that BmNPV could increase the expression of miR‐275‐5p by inhibiting cellular Lnc_209997 expression to promote their own proliferation. Our results are helpful for better understanding the role of lncRNAs in BmNPV infection, and provide insights into elucidating the molecular mechanism of interaction between Bombyx mori and virus. Abstract : The speculated mechanism of Lnc_209997 on BmNPV proliferation. It was speculated that BmNPV infection resulted in down‐regulation of Lnc_209997 expression, which alleviated the interaction between Lnc_209997 and miR‐275‐5p and led to release of more miR‐275‐5p, which can modulate important signalling pathways by regulating host or viral genes and thus promoted the proliferation of BmNPV.